Energy Efficiency Study in Lebanon - World Bank (Washington, DC, 2013)
The purpose of this report is to assess the status of past and current energy efficiency initiatives in Lebanon and, in conjunction with key stakeholders, prepare an Energy Efficiency Action Plan, implementation of this Action Plan in the near future. The identified EE programs have been developed based on available data and information gathered during our one-week field mission and the best practices in similar countries with comparable backgrounds. The savings and investments for each proposed program have been evaluated outlining the impacts of the expected emission reductions and of the expected primary energy savings. The major design phases of each program, their implementation, monitoring plans, and evaluation have been defined. Program financing sources have been recommended and enumerated for possible consideration during the development phase. The role of the various stakeholders has also been determined for each program with general recommendations and suggestions for the successful implementation of the programs. Actions plans are recommended, and it is recommended to begin with the short-term action plan, however the other proposed plans could be started, especially in the case where related actions have already been initiated, to ensure their continuity and the effective development of the proposed programs.